Recombinant Human Matrix Metalloproteinase‐2 Impairs Cardiovascular β‐Adrenergic Responses. (29th September 2012) - Ferraz, Karina C.; Sousa‐Santos, Ozélia; Neto‐Neves, Evandro M.; Rizzi, Elen; Muniz, Jaqueline J.; Gerlach, Raquel F.; Tanus‐Santos, Jose E.
Abstract: Growing evidence supports the involvement of matrix metalloproteinases (MMPs) in the pathogenesis of many cardiovascular diseases. Particularly, imbalanced MMP‐2 activity apparently plays a critical role in cardiovascular remodelling. While some studies have suggested that MMP‐2 may affect the vascular tone and impair β‐adrenoreceptor function, no previous study has examined the acute haemodynamic effects of MMP‐2. We examined the effects of recombinant human MMP‐2 (rhMMP‐2) administered intravenously to anaesthetized lambs at baseline conditions and during β1 ‐adrenergic cardiac stimulation with dobutamine. We used 26 anaesthetized male lambs in two study protocols. First, rhMMP‐2 (220 ng/kg/min. over 60 min.) or vehicle was infused in the lambs, and no significant haemodynamic changes were found. Therefore, we infused dobutamine at 5 μg/kg/min. i.v. (or saline) over 180 min. in lambs that had received the same rhMMP‐2 infusion preceded by doxycycline i.v. at 10 mg/kg (or saline). Plasma and cardiac MMP‐2 levels were assessed by gelatin zymography, and gelatinolytic activity was assessed by spectrofluorimetry. Dobutamine decreased systemic vascular resistance index, and this effect was attenuated by rhMMP‐2 infusion. Moreover, dobutamine increased the cardiac index and left ventricular dP / dt max, and these effects were attenuated by rhMMP‐2. The previous administration of doxycycline blunted rhMMP‐2‐induced changes in dobutamine responses. While the infusion of rhMMP‐2 did not increase plasma and cardiac MMP‐2 levels, it increased cardiac gelatinolytic activity, and doxycycline blunted this effect. Our findings show that rhMMP‐2 exerts no major haemodynamic effects in lambs. However, rhMMP‐2 impairs the responses elicited by activation of β‐adrenoreceptors.